Tumor-associated neutrophils and macrophages interaction contributes to intrahepatic cholangiocarcinoma progression by activating STAT3 - Jian Zhou; Jia Fan; Zhiqiang Hu; Jia Li; Zhengjun Zhou; Pengcheng Wang; Rongqi Sun; Haoyang Xin; Chubin Luo; Shaolai Zhou (Journal for ImmunoTherapy of Cancer)
Background Tumor-associated neutrophils (TANs) and macrophages (TAMs) can each influence cancer growth and metastasis, but their combined effects in intrahepatic cholangiocarcinoma (ICC) remain unclear.Methods We explored the distributions of TANs and TAMs in patient-derived ICC samples by multiplex immunofluorescent staining and tested their separate and combined effects on ICC in vitro and in vivo. We then investigated the mechanistic basis of the effects using PCR array, western blot analysis and ELISA experiments. Finally, we validated our results in a tissue microarray composed of primary tumor tissues from 359 patients with ICC.Results The spatial distributions of TANs and TAMs were correlated with each other in patient-derived ICC samples. Interaction between TANs and TAMs enhanced the proliferation and invasion abilities of ICC cells in vitro and tumor progression in a mouse xenograft model of ICC. TANs and TAMs produced higher levels of oncostatin M and interleukin-11, respectively, in co-culture than in monoculture. Both of those cytokines activated STAT3 signaling in ICC cells. Knockdown of STAT3 abolished the protumor effect of TANs and TAMs on ICC. In tumor samples from patients with ICC, increased TAN and TAM levels were correlated with elevated p-STAT3 expression. All three of those factors were independent predictors of patient outcomes.Conclusions TANs and TAMs interact to promote ICC progression by activating STAT3.